O efeito dos filhos sobre a participação feminina no mercado de trabalho brasileiro: explorando diversas fontes de variação exógena na fecundidade - Laeticia Rodrigues de Souza (2009)
The rapid decline in fertility and, at the same time, the increase of female labor force participation in the last few decades motivated studies focusing on the relationship between fertility and labor force decisions. The goal of this dissertation is to investigate the children-work relationship for females However, more than measuring this association, we are interested in estimating the effect of the children on female labor force participation, considering the trends in the relation over time. The impact of fertility decisions on ones professional career has many dimensions: it may lead them to quit working (temporarily or definitely), induce them to reduce working hours or even to cause them to change their occupation or market segment. In addition, it can delay their promotion to better jobs and wage increases (Maron & Meulders, 2007). In addition, based on the fact that each child may present a different effect upon the mothers labor supply decision, for example, the first child is the one has a stronger effect on the entrance or permanence of the mother in the labor market (Lérida, 2006). We have estimated, separately, the effect of the first, the second and the third (or above) children on female labor force participation. However, due to the fact that having children and working are, normally, simultaneous decisions, estimating the effect of the children upon their participation in the market does not constitute a trivial task, as the traditional methods do not allow us to estimate this effect, but only the association among these variables. Thus, we have estimated the effect of the children based on variables that affect the fertility and that only affect the female labor supply by means of the fertility, which eliminates the problem of the children-women labor endogeneity. We find that children reduce the probability of a woman to enter the labor force and that this effect is stronger for the first and third (or more) children. Moreover, between the decades of 1990 and 2000, the negative effect of the children on female labor supply diminished.